Workflows and locations matter - insights from electronic hand hygiene monitoring into the use of hand rub dispensers across diverse hospital wards - Christoph Senges; Christiane Herzer; Erlandas Norkus; Marco Krewing; Clara Mattner; Leonard Rose; Tobias Gebhardt; Frauke Mattner; Heide Niesalla (Elsevier, 2024)
Summary: Background: While healthcare-associated infections (HAIs) affect approximately 3.2-6.5% of hospitalised patients in the US and Europe, improving hand hygiene (HH) could reduce HAI rates. Investigating HH is time-consuming and not always objective, and comprehensive, unbiased data is needed to develop effective strategies. Using electronic tools can provide new and detailed insights on the determinants of HH. Aim: To evaluate location-dependent usage of wall-mounted dispensers (WMDs) and point-of-care dispensers (POCs) using an electronic HH recording system. Methods: In this retrospective study, hand rub volumes were anonymously recorded for 931,446 disinfections from 17 wards in nine German hospitals using the electronic monitoring system NosoEx®. Number of disinfections and rub volumes of WMDs/POCs by ward and room type were analysed. Findings: Generally, WMDs were most prevalent. With >3 dispensers per bed and >20 disinfections per patient day, availability and use were highest in intensive care (ICU) and intermediate care (IMC), but here rub volumes from WMDs were lowest (∼2.0 mL). Although most dispensers are located in patient rooms (∼42%), they are more frequently used in hallways. In surgical ICUs, dispensers are often used in patient rooms, where contact with open wounds is common. About 3.6 mL of hand rub is used per disinfection in treatment rooms, the highest volume of all room types. Conclusion: Dispenser use was dependent on location, room type, ward specialisation and workflow. Optimising the location of hand rub dispensers (HRDs)s is not the only solution to improve HH, but can help reduce inconvenience, achieve more ergonomic workflows and better meet user needs.